Women’s rights in marriage: between Qur’ānic provision and malpractice - Ahmad, Nadzrah; Ghazali, Norzulaili; Othman, Roslina; Ismail, Nurul Syuhada (Universiti Putra Malaysia Press, 2019)
Women’s rights issues have marked its spot as one of the most debated issues throughout centuries. Marriage is regularly portrayed as an “oppressive sphere” for women, with their rights being oppressed the moment they enter a marriage contract, especially in Islam. However, further reflection on the issue has shown that Islamic matrimony liberates women, preserves their honour and place in society, and abolishes injustice, when guided in principle from the Qur’an and Sunnah of Prophet Muhammad (PBUH). Regrettably, Muslim’s misunderstanding due to cultural interpretation and malpractice of original Islamic teachings has tainted the true Islamic ideal. In dealing with the data, the study utilised an inductive method and content analysis, and aimed to draw attention to the misunderstandings of marriage in Islam with regards to women’s rights. Further discussion would serve to explore the outcome of women’s rights in marriage as bestowed by Islam, and understand the importance of the marriage institution, whilst examining the compelling misunderstandings by detractors.